PENERAPAN PROTOKOL KESEHATAN PADA ACARA HAJATAN MASYARAKAT DI LINGKUNGAN MALLEKANA KELURAHAN TETTIKENRARAE, KECAMATAN MARIO RIWAWO, KABUPATEN SOPPENG: Application Of Health Protocols At The Community Celebration Event In The Mallekana Neighborhood, Tettikenrarae Sub-District, Mario Riwawo District, Soppeng Regency - Raymond Arief; Base, Nurul Hidayah (JURNAL PENGABDIAN MASYARAKAT YAMASI, 2022)
The very fluctuating increase in Covid-19 cases has made the implementation of healthprotocols more active. The government has issued a Policy for the Enforcement of Community ActivityRestrictions (PPKM) on a micro basis from February 9 to 22, 2021. The wedding celebration is a placethat has great potential to increase the spread of Covid-19 in the community. The application of Healthprotocols during the Covid-19 pandemic is very important to prevent the transmission of Covid-19,especially at bridal celebrations. The implementation of the Health protocol to the community is carriedout to get used to implementing the 3M (Wearing masks, Keeping distance, and Washing hands withsoap). The socialization begins by providing information orally or by distributing information leaflets toinvited guests on the night of Mappacci and on the day of the Marriage Contract, directing them to washtheir hands properly using hand soap and or prepare hand sanitizers, distributing masks, and adjustingthe distance between chairs so that social distancing is maintained. stay awake. The implementation ofthe health protocol at the wedding ceremony was supported by the Soppeng district government, with acircular from the National Disaster Management Agency for the Soppeng Regency Covid-19 Task Force.In general, the people in the Mallekana neighborhood were able to implement the 3M health protocolswell, although a small portion of them still had a crowd at the time of the marriage ceremony. However,after being given verbal warnings, the community can obediently keep their distance and adhere to theprotocols conveyed